2016
DOI: 10.1002/sia.6058
|View full text |Cite
|
Sign up to set email alerts
|

In situ PM‐IRRAS studies of organothiols and organosilane monolayers–ZnO interfaces at high water activities

Abstract: In situ photoelastic-modulated Fourier transform infrared reflection absorption spectroscopy has been applied for the investigation of interfacial stability of organothiol and organosilane monolayer films on nanocrystalline zinc oxide thin films. It has been shown that for octadecyltriethoxysilane films, exposure to high water activities results in physisorption of water in the crosslinked film. This high water activity at the interface leads to a reversible wet de-adhesion of the interfacial silanol groups fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“… 73 The release of alkylorganosilanes was reported by Torun and co-workers, who revealed that alkylorganosilanes anchor by few points on ZnO surface leading to a small number of covalent bonds. 53 Thereby, well ordered DMOAP monolayers might not be suitable for antibacterial coatings since the quaternary ammonium groups are not easily accessed by the bacteria membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 73 The release of alkylorganosilanes was reported by Torun and co-workers, who revealed that alkylorganosilanes anchor by few points on ZnO surface leading to a small number of covalent bonds. 53 Thereby, well ordered DMOAP monolayers might not be suitable for antibacterial coatings since the quaternary ammonium groups are not easily accessed by the bacteria membrane.…”
Section: Resultsmentioning
confidence: 99%
“…40,51,52 Starting from a long-chain alkyltrialkoxysilane, such as octadecyltriethoxysilane (ODS) on zinc oxide surfaces, the formation of Si-O-Si was reported to dominate the formation of Si-O-Zn bonds, leading to a crosslinked siloxane network that adheres on the substrate surface via hydrogen bonding or with few anchoring points along the surface. 53 Interestingly, acidic properties of both zinc oxide and titania are related to Lewis acid surface sites rather than to Bronsted sites. 52,54 The complexation of the acidic substrate surface sites with oxoanions or esters may be driven by Lewis basic electron pair donor properties of the respective adsorbent providing the oxo-bridge.…”
Section: Xps Characterizationmentioning
confidence: 99%
“…Although the bonding mechanism illustrated in Figure has been often cited in the literature, reactions (c,d) in the mechanism, which involve the actual interactions between the silanes and the substrate, are still under debate. On the one hand, it is questioned whether SiOM + fragments obtained from ToF-SIMS measurements can be considered as sufficient evidence for covalent bonding. , On the other hand, direct evidence for hydrogen bond interactions at the metal oxide–silane interface has never been provided. In this work, ToF-SIMS will be applied to study the bonding mechanism of aminopropyl triethoxysilane (APS) on steel.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it is questioned whether SiOM + fragments obtained from ToF-SIMS measurements can be considered as sufficient evidence for covalent bonding. 3,10 On the other hand, direct evidence for hydrogen bond interactions at the metal oxide− silane interface has never been provided. In this work, ToF-SIMS will be applied to study the bonding mechanism of aminopropyl triethoxysilane (APS) on steel.…”
Section: Introductionmentioning
confidence: 99%
“…Reports in this direction are usually restricted to the adsorption of long chain molecules (12-18 carbon atoms) on monocrystalline ZnO surfaces. [47,48] It is also important to note that macroscopic assemblies of ZnO are generally polycrystalline, an aspect that has been largely overlooked in previous studies. In a seminal work, Perkins showed that the thermal stability of n-hexanethiol SAMs on polycrystalline ZnO surfaces was lower than that of their phosphonic acid counterparts.…”
Section: Introductionmentioning
confidence: 99%